Clinical diagnosis of bovine granulosa cell tumour in a Holstein cow using plasma anti-Müllerian hormone concentration: a case report. Issue 1 (1st January 2017) - Okawa, Hiroaki; Tomiki, Motohisa; Ishida, Tsuyoshi; Kawaguchi, Hiroaki; Wijayagunawardane, Missaka P. B.; Takagi, Mitsuhiro
ABSTRACT: A 23-month-old Holstein cow had a multi-cystic and enlarged left ovary detected by rectal palpation and ultrasonography. The plasma anti-Müllerian hormone (AMH) concentration was 36.5 ng/ml, which is higher than normal. From the clinical history and plasma AMH levels, a granulosa cell tumour (GCT) was diagnosed. Affected ovary was removed by ovariectomy, and GCT was confirmed with histopathological findings. The cow was artificially inseminated at 145 days after ovariectomy, and conceived. The plasma AMH concentration declined at 224 days after removal of affected ovary to less than 0.1 ng/ml, and recovery of fertility was achieved. In conclusion, measurement of plasma AMH levels combined with rectal palpation and ultrasonography examinations could be useful in clinical diagnosis of bovine GCT.